Análise multivariada dos fatores determinantes da mortalidade perinatal de fetos submetidos à transfusão sanguínea intrautero por anemia decorrente da isoimunização materna - Gabriel Costa Osanan (2010)
Isoimmunization is the main cause of fetal anemia in Brazil and it is an important cause of preventable perinatal mortality and morbidity.Objective: To determine prognostic factors of perinatal mortality in transfused fetuses. Patients and methods: It is a cohort study that followed 128 pregnancies complicated by maternal isoimmunization, in which their fetuses had to receive intrauterine transfusion at the CEMEFE-HC-UFMG, during the period of 1999-2009. The prognostic factors of perinatal mortality were allocated into three distinct categories: that related to prematurity, that related to fetal anemia and that related tothe IUT. Each prognostic factor was individually tested by the univariate analysis. Then, one significative variable of each category was selected to compose the multivariate analysis. In this analysis, it was obtained from each prognostic factor: Z score, p value, likelihood ratio and 95% confidence intervals. Results: The mortality rate found in this study was 18, 1%, and most of them occurred during the intrauterine period (17 out of 25). After the univariate analysis, the following factors were chosen to compose the multivariate analysis equation: the gestational age atbirth ( p<0,0001 ), the presence of intrauterine transfusion ( IUT ) complications ( p < 0,0001 ) and the hemoglobin deficit at the last IUT ( p = 0,001 ). The multivariate analysis indicated that all of these three parameters were significant to determine death in following order of importance: gestational age at birth (z score: -3,56; p< 0,0001) , presence IUT complications (z score: 2,41; p = 0,016) , and hemoglobin deficit at the last cordocentese ( z score: 2,13; p = 0,033). Conclusion: Prematurity,represented by gestational age at birth, was the most important factor to determine perinatal mortality in the group of transfused fetuses. IUT complications and the severity of fetal anemia at the last transfusion were also significant as an indicator of perinatal mortality prognosis.